Gestão do Almoxarifado Central da Universidade Federal da Paraíba: diagnóstico situacional por meio de documentos institucionais - Silva, Genilson Lima e (2022)
The main purposes of Public Management is to allow the government's objectives to be achieved through the provision of services to citizens. In this context, the essential functions and directly linked to the country's development is education. Therefore, Federal Institutions of Higher Education occupy an important space by contributing to the professionalization and dissemination of knowledge to the community. In recent years, with the expansion of vacancies in these institutions, there has also been an increase in costs. Thus, proper control of material stock through warehouse management becomes essential to reduce budgetary impacts, promote improvements in management practices and contribute to institutional efficiency. Thus, this study aimed to elaborate a situational diagnosis of stock management in the UFPB central warehouse based on selected institutional documents. Therefore, the theoretical framework of this work includes the theme of public management; history of institutions and higher education in Brazil; management of higher education institutions; management of materials in the public service and management of warehouses. This research is of the applied type, with a qualitative approach and descriptive and exploratory character, which uses bibliographic and documentary research techniques. In possession of institutional documents referring to the central warehouse, Bardin's content analysis was chosen to categorize the information collected, with subsequent comparative analysis of the examined contents. The results were divided into four categories: General characteristics and Work process; Receipt of materials; Storage and Delivery. These denote the work process in the chosen location, enabling the situational diagnosis. From this, it was possible to conclude that the stock management of materials received at the UFPB central warehouse has advanced in recent years. However, the need for improvements and modifications to the environment is highlighted; incentive for training employees on the work carried out specifically in warehouses; and availability of vehicle and equipment, which influence the storage and delivery of items to the requesting sectors. It is expected that the diagnosis will support institutional and local management decision-making, assisting in the work process and in the efficiency of the sector, which makes it possible to distribute the material for the execution of teaching, research and extension activities within the scope of the UFPB.